Infantile Alexander’s disease - Selvamani, Dhanraj; Patra, Bijoy; Arora, Suryansh; Chumber, Shishir; Vani, Kavita (International Journal of Contemporary Pediatrics, 2023)
Alexander disease is a rare, progressive debilitating disorder that affects the nervous system and causes significant neurological problems and developmental delays. The symptoms of Alexander disease vary depending on the type and severity of the disorder, but they typically include developmental delay, intellectual disability, seizures and progressive neurological problems such as spasticity, weakness and ataxia. The proband is a case of a 9-month-old boy presenting with macrocephaly and neuroregression. Magnetic resonance imaging (MRI) revealed hyperintense signal in white matter with predominant involvement of frontal white matter, ventriculomegaly and involvement of basal ganglia, brainstem and cerebellum. The diagnosis was confirmed on genetic analysis. Alexander’s disease is a rare neurodegenerative condition that characteristically presents with macrocephaly and high T2 signal in frontal white matter in infants.